Japonska družba danes - Ferfila, Bogomil (Teorija in praksa, 1999)
It is actually quite difficult to present a particular state or its content - society. There is a lot of jeopardy and possible mistakes: some characteristics may be chosen as key indicators, but in fact they are not; some which are important may not be stressed enough; others may be overlooked,although they ought to be at least pointed out, being connected with other key characteristics etc. One of the possible approaches is to imagine a particular country as an average citizen with all characteristics most frequently present. Every state or its society is something special, since it is impossible to find two countries at the same level of development according to all their characteristics (history, religion, climate, economical-developmental indicator, socio-cultural characteristics etc.). However, Japan is a unique country also according to inhabitants' belief that they are something special. Doubtless, the characteristics of homogeneity, egalitarianism, orientation toward group and collective values are strong and prevailing. However, one cannot forget about several subcultures - if understood as sets of values, expectations and the ways of life lived and shared by a certain part of population. They are connected with racial division of Japanese society, and also with sex, age, religion, vocation etc. This is connected with differences in limited access to numerous resources, including economic privileges, political power, social reputation, information, knowledge. In this context Japanese society has to be seen as a society of several cultures and strata. Although Japan is racially and nationally homogeneous, it has series of minorities, which are by the rule an object of discrimination and prejudices, rising from a culturally defined ethnical myths, illusions, falseness.
Keywords: Japonska; družba; society; culture; kultura; subculture; subkultura; vrednote; konvergenca; družbena stratifikacija